Factores que inciden en el pago de los impuestos de los expendedores de ropa del centro comercial ferroviario, ubicado en el Cantón Ambato, Provincia De Tungurahua, 2017 - Caguana Paste, Mónica Jacqueline (2019)
Tax noncompliance at payment is one of the main events that affects tax collection, since it produces the scarcity of necessary resources to guarantee the public sustainability services. All people who carry out an economic activity in the country are subject to legal regulations that oblige them to comply taxes payment; the State will be distributed to the entire population in representation of the country jobs. In the commercial railway center, the merchants do not have knowledge about their tax obligations and this causes that they do not reach collection levels wished by the tributary authority, on the other hand, they are exposed to fines and sanctions. The investigation objective was to determine the factors that influence the taxes payment of the clothing retailers of railway commercial center, located at Ambato canton, Tungurahua province, 2017. During the investigation, the quantitative methodology was applied where they were analyzed. And they interpreted the results, allowing to acquire fundamental knowledge due to the fact that data was collected with quantifiable information, at the same time the investigation technique was used as the survey, being this one of great help, because it was useful on compilation process of information. According to the results, it was possible to identify the causes for which the majority of taxpayers do not comply with their taxes on time, this is due to their negligence and incompetence of formal tax duties, which could cause the disqualification of their commercial activities and an economic instability. Also, it was determined that the factor that has prevented from fulfilling their obligations, is ignorance, it is concluded that the breach of tax duties caused incidence on taxes payment, since many have been sanctioned, causing serious economic effects.